Effects of lorazepam and baclofen on short‐ and long‐latency afferent inhibition. (3rd October 2018) - Turco, Claudia V.; El‐Sayes, Jenin; Locke, Mitchell B.; Chen, Robert; Baker, Steven; Nelson, Aimee J.
Abstract : Key points: Short‐latency afferent inhibition (SAI) is modulated by GABAA receptor activity, whereas the pharmacological origin of long‐latency afferent inhibition remains unknown. This is the first study to report that long‐latency afferent inhibition (LAI) is reduced by the GABAA positive allosteric modulator lorazepam, and that both SAI and LAI are not modulated by the GABAB agonist baclofen. These findings advance our understanding of the neural mechanisms underlying afferent inhibition. Abstract: The afferent volley evoked by peripheral nerve stimulation has an inhibitory influence on transcranial magnetic stimulation induced motor evoked potentials. This phenomenon, known as afferent inhibition, occurs in two phases: short‐latency afferent inhibition (SAI) and long‐latency afferent inhibition (LAI). SAI exerts its inhibitory influence via cholinergic and GABAergic activity. The neurotransmitter receptors that mediate LAI remain unclear. The present study aimed to determine whether LAI is contributed by GABAA and/or GABAB receptor activity. In a double‐blinded, placebo‐controlled study, 2.5 mg of lorazepam (GABAA agonist), 20 mg of baclofen (GABAB agonist) and placebo were administered to 14 males (mean age 22.7 ± 1.9 years) in three separate sessions. SAI and LAI, evoked by stimulation of the median nerve and recorded from the first dorsal interosseous muscle, were quantified before and at the peak plasma concentration following drug ingestion. Results indicate that lorazepam reduced LAI by ∼40% and, in support of previous work, reduced SAI by ∼19%. However, neither SAI, nor LAI were altered by baclofen. In a follow‐up double‐blinded, placebo‐controlled study, 10 returning participants received placebo or 40 mg of baclofen (double the dosage used in Experiment 1). The results obtained indicate that SAI and LAI were unchanged by baclofen. This is the first study to show that LAI is modulated by GABAA receptor activity, similar to SAI, and that afferent inhibition does not appear to be a GABAB mediated process. Key points: Short‐latency afferent inhibition (SAI) is modulated by GABAA receptor activity, whereas the pharmacological origin of long‐latency afferent inhibition remains unknown. This is the first study to report that long‐latency afferent inhibition (LAI) is reduced by the GABAA positive allosteric modulator lorazepam, and that both SAI and LAI are not modulated by the GABAB agonist baclofen. These findings advance our understanding of the neural mechanisms underlying afferent inhibition.